Persistent Hyperactivation of Endothelial Cells in Patients with Alcoholic Hepatitis. (21st April 2020) - Xia, Ying; Yang, Jing; Sanyal, Arun J.; Shah, Vijay H.; Chalasani, Naga P.; Yu, Qigui; Zheng, Xiaoqun; Li, Wei
Abstract : Background: Alcoholic hepatitis (AH) is a severe inflammatory liver disease that develops in some heavy drinkers. AH patients have intense hepatic infiltration of leukocytes. Up‐regulation of cell adhesion molecules (CAMs) upon endothelial cell (EC) activation plays an important role in leukocyte transendothelial migration. CAMs can shed from EC surface and accumulate in the blood, serving as soluble markers for EC activation. In this study, we examined the impact of heavy drinking on expression of soluble forms of EC activation markers (CD146, ICAM‐1, VCAM‐1, and VEGF‐A) and the effect of alcohol abstinence on the reversal of these abnormalities in heavy drinkers with and without AH. Methods: ELISA and multiplex immunoassays were used to measure soluble EC activation markers in plasma samples from 79 AH patients, 66 heavy drinkers without overt liver disease (HDC), and 44 healthy controls (HC) at baseline, 31 AH patients and 30 HDC at 6‐month follow‐up, and 18 AH patients and 25 HDC at 12‐month follow‐up. Results: At baseline, the 4 soluble markers were significantly up‐regulated in AH patients compared with HDC and HC, whereas only sVCAM‐1 was elevated in HDC relative to HC. At follow‐ups, plasma levels of CD146, VCAM‐1, and VEGF‐A remained higher in AH patients, even for those who stopped drinking. These dysregulated markers correlated with AH disease severity, clinical parameters, and several soluble inflammatory factors. Conclusions: The levels of soluble CD146, ICAM‐1, VCAM‐1, and VEGF‐A were highly elevated in AH patients, and alcohol abstinence did not completely reverse these abnormalities. Abstract : Patients with alcoholic hepatitis (AH) have intense hepatic infiltration of leukocytes mostly mediated by the upregulation of cell adhesion molecules (CAMs) upon endothelial cell (EC) activation. CAMs shed from ECs accumulate in circulation, serving as soluble markers for EC activation. Here, we found that the levels of soluble EC activation markers CD146, ICAM‐1, VCAM‐1, and VEGF‐A were highly elevated in AH patients, compared to heavy drinking controls (HDC) and healthy controls (HC). Alcohol abstinence did not completely reverse these abnormalities.